Desempenho agronômico do coquinho azedo em cinco safras - Ana Paula Rocha Souza (2016)
The sour coquinho, Butia capitata (Mart.) Becc., is a native palm of the Brazilian Cerrado. Its fruits are exploited in extractive form and used in fresh consumption and the manufacture of juices, ice cream and popsicles. Studies on the domestication of plants can ensure a more rational exploitation and contributing to the preservation of the species. In this sense, the present study was to evaluate the agronomic performance of sour coquinho grown in monoculture system during five seasons. The orchard, installed in Montes Claros - MG, consisting of 30 plants five years old, was evaluated weekly during five seasons, from July/2010 to June/2015. They evaluated the number of issued inflorescences harvested bunches, fruits per bunch, rachilles, basal female flowers, middle, apical and total and length and diameter of the flowers and fruits, bunch weight, fruit weight of the bunch, and production/plant/year, and still the vegetative characteristics: plant height and diameter and length and width of the third issued sheet. The design adopted was completely randomized, and each plant was considered a repeat and the five crops treatments. The flowering occurs in higher concentration between the months of April to November, while production is from July to February. The production per plant increases over time, due to the higher number of fruits per bunch, which is also a consequence of the increase in the number of flowers, especially those located in the middle and apical region of the inflorescence. The plant sour coquinho in monoculture and ten years old can produce per harvest 15 kg of fruits per individual. Plants with larger diameter and height issued increasing sheets and are more productive. The cultivation of the coquinho is an interesting alternative to expand the supply of fruit and ensuring higher productivity and economic return to the producer.